2022
DOI: 10.1155/2022/8337048
|View full text |Cite
|
Sign up to set email alerts
|

NAV3 Is a Novel Prognostic Biomarker Affecting the Immune Status of the Tumor Microenvironment in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors in the world. Tumor microenvironment (TME) plays a crucial role in the development of CRC. With the deep understanding of TME function, growing studies have demonstrated that alteration in tumor-infiltrating immune cells (TICs) and gene expressions are associated with clinical outcomes of various tumors. In this study, we aimed to recognize critical prognostic genes involved in immune states in TME of CRC. Hence, the proportion of TICs and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The biological functions of these genes involved in our signature have been elucidated more or less in previous studies. It was shown that the high levels of ZNF385A, LAMP, CADM3, NAV3, and NLGN1 indicate the poor prognosis of CRC patients (Martinez-Romero et al, 2018;Chang et al, 2021;Chen et al, 2021;Yu et al, 2021;Li et al, 2022), and these results were in accordance with our findings. Similarly, low expressions of CYTH3, NOVA1, and EPHA6 were highly correlated with longer OS in patients with other types of cancers (Zhang et al, 2014;Zhou et al, 2018;Xu et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The biological functions of these genes involved in our signature have been elucidated more or less in previous studies. It was shown that the high levels of ZNF385A, LAMP, CADM3, NAV3, and NLGN1 indicate the poor prognosis of CRC patients (Martinez-Romero et al, 2018;Chang et al, 2021;Chen et al, 2021;Yu et al, 2021;Li et al, 2022), and these results were in accordance with our findings. Similarly, low expressions of CYTH3, NOVA1, and EPHA6 were highly correlated with longer OS in patients with other types of cancers (Zhang et al, 2014;Zhou et al, 2018;Xu et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…3E to J ). SRRM4 is a known regulator of alternative splicing, while NAV3 is reported to be involved in multiple immune and infection-associated pathways such as FoxO signaling, T cell activation, and Human papillomavirus infection pathways ( 24 , 25 ). Therefore, we propose that the promoter region may play an important role in shaping the alternative transcription vis-à-vis disease severity in COVID-19 disease.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have reported association in some other diseases as well. For example, SRRM4 and NAV3 are reported to regulate lung cancer and colorectal cancer, respectively ( 24 , 45 ). The European Molecular Biology Laboratory (EMBL) expression atlas shows their expression in different tissues, such as non-endothelial lung cells as well as other tissues in the lungs and gastrointestinal tract, in addition to the neuronal tissues.…”
Section: Discussionmentioning
confidence: 99%